Margin failures in crown-like brittle structures: Off-axis loading - Ford, Christopher; Qasim, T.; Bush, M.; Hu, X.; Shah, M.; Saxena, V.; Lawn, B. (John Wiley & Sons, Inc., 2008)
The effect of off-axis loading of compliant indenters on the initiation of cracks at the margins of dental crown-like dome structures consisting of glass shells back-filled with an epoxy resin is examined. As in previous studies on similar structures but with strictly axial loading, cracks can be made to initiate and propagate from the margins around the dome faces into a "semi-lunar" fracture pattern characteristic of some all-ceramic crown failures. In this study, balsa wood and teflon disk indenters are used to provide the off-axis loading, at 45° to the dome axis. The soft indenters, considered representative of food bolus, spread the contact at the top surface, suppressing otherwise dominant radial cracks that ordinarily initiate at the dome undersurface directly along the load axis beneath harder indenters. Finite element modeling is used to show that off-axis loading dramatically increases the tensile stresses at the near-side dome margin, strongly diminishing the loads required to generate the lunar fracture mode.